The Economist’s Narrative On the End of the Afghanistan War and Its Implications for US Global Standing - Ishpekova–Bratanova, Kalina (UNWE Yearbook, 2023)
This paper attempts to survey key assessments of the causes and consequences of the strategic failure of American foreign policy in Afghanistan, without giving a comprehensive or detailed account of all proximate and longer-term causes for the US changing stance in international affairs after this withdrawal. To this end, it summarizes the opinions of eminent experts in the field of foreign policy and international relations that were invited to participate in the Economist’s special rubric on the aforementioned topic. The findings suggest that there are agreed upon reasons for the United States’ failure in Afghanistan, among which is the impossible mission of exporting democracy to this country as well as America’s refusal to engage in creative diplomacy.
Keywords: Narratives; Foreign policy; International relations; Discourse analysis